Studi Kemampuan Literasi Kimia Peserta Didik pada Materi Hidrokarbon: Kasus Senyawa Toksik Pada Gorengan - Faiz Ilham Pratama; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2023)
Chemical literacy has become an important issue to be discussed, making students aware of the benefits of literacy, becoming the main goal for educators, scientists, and curriculum policy makers. Chemical literacy is important for students because it equips students to make decisions, makes students more critical, creative, and helps them in solving everyday problems or natural phenomena based on their knowledge. This study aims to describe the chemical literacy abilities of students on hydrocarbon materials with the topic of discourse on the case of toxic compounds in fried foods. This research includes quantitative descriptive research. The population in this study were all students of class 11st at a public high school in Magelang City who had studied hydrocarbons. The number of samples from this study was 100 students taken from three classes. The data collection technique in this research is a questionnaire. The data research instrument used was a student questionnaire sheet which was a closed questionnaire with four choices, namely SD (Strongly Disagree), D (Disagree), A (Agree), and SA (Strongly Agree). The results of the research that has been done can be seen that the chemical literacy ability of students on hydrocarbon materials is 63.1875%. These results indicate that the chemical literacy ability of students on chemical hydrocarbons is fair. The results of the research that has been done can be seen that the chemical literacy ability of students on hydrocarbon materials is 63.1875%. These results indicate that the chemical literacy ability of students on chemical hydrocarbons in fair catagory.